La figura dello straniero nella Bibbia Ebraica: fenomenologia e teologia - Bovati, Pietro (The Biblical Annals, 2023)
The introduction of the article presents some methodological clarifications that aim to achieve a proper thematic treatment of the foreigner in the Bible. It (a) states the need to place the study of terms that indicate the foreigner in the relevant semantic field, (b) stresses the importance to be accorded to the founding narratives, and (c) indicates the value of the term “figure” as applied specifically to the immigrant. The contribution is then divided into three sections: 1. “The Phenomenology of the Foreigner in the Bible” shows the criteria for defining the foreigner, and emphasises the specific notion of the immigrant; 2. “The Biblical Theology of the Immigrant” illustrates the precariousness of the one who requests hospitality and, at the same time, makes manifest the divine blessing for the one who welcomes him. 3. “The Biblical Norms Regarding the Immigrant” show how different precepts tend to equate the immigrant with the citizen itself.